'Does Africa not deserve shiny new cities?' The power of seductive rhetoric around new cities in Africa. (September 2019) - Côté-Roy, Laurence; Moser, Sarah
This paper explores the emerging new master-planned city-building trend on the African continent. Situating our research within urban policy mobilities literature, we investigate the 'Africa rising' narrative and representation of Africa as a 'last development frontier' and 'last piece of cake', an imaginary that provides fertile ground for the construction of new cities. Building upon research on the practices of 'seduction' that facilitate urban policy circulation, we argue for the relevance of critically examining elite stakeholder rhetoric to understand the relative ease with which the new city development model is being promoted in Africa. We investigate the enablers, advocates and boosters of new cities, represented mainly by states, corporations, non-profits and consultants to render visible the complex networks of relations and private interests that support and enable the creation and circulation of the new cities model in Africa. We also analyse the pervasive 'right to development' argument among African elites, which precludes criticism of new city ventures and circulates problematic assumptions about modernity and development. We conclude by discussing how stakeholder rhetoric limits the range of urban visions that are put into circulation and mobilized for Africa's urban future.